Why scapegoating can ruin an apology: The mediated-moderation model of appropriate crisis response messages in the context of South Korea - Youk, Sungbin; Park, Hee Sun (Frontiers in Psychology, 2023)
Theory-driven recommendations for crisis response messages may fall short in practice when cultural and normative complexities are overlooked. South Korean companies frequently use apologies across various crisis situations and pair them with other types of crisis response strategies (i.e., scapegoating). This study stretches the boundaries of crisis communication literature by a) empirically testing the effectiveness of crisis communication in a non-Western culture, b) examining various content of apologies, and c) integrating the theory of communicative responsibility and situational crisis communication theory to better understand the psychological state of the receivers of the crisis response messages. The findings indicate that an apology that is provided with compensation is more appropriate than those with scapegoating. The appropriateness is moderated by the perceived symmetry in communicative responsibility, and fully mediates the relationship between apology type and reputation.